Is ankyloglossia associated with obstructive sleep apnea? - Bussi, Marieli Timpani; Corrêa, Camila de Castro; Cassettari, Arthur Justi; Giacomin, Lorena Torres; Faria, Ana Célia; Moreira, Ana Paula Sereni Manfredi; Magalhães, Itamá; Cunha, Mila Oliveira da; Weber, Silke Anna Theresa [UNESP]; Zancanella, Edilson; Machado Júnior, Almiro José (Elsevier, 2021)
Objectives: To investigate the evidence on the association between ankyloglossia and obstructive sleep apnea. Methods: An integrative literature review was carried out in the databases. Observational and interventional studies that assessed the lingual frenulum in children with sleep-disordered breathing were included. As exclusion criteria: studies in animals, in vitro, letters to the editor, expert opinions, other reviews. The selected articles were analyzed regarding the study design, sample, characterization of the lingual frenulum and sleep assessment, in addition to the main results and conclusions. Results: Ninety-seven articles were identified, but only 4 met the inclusion criteria. Two retrospective studies concluded that the untreated shortened lingual frenulum at birth is associated with obstructive sleep apnea. A prospective study concluded that there was an improvement in speech and deglutition after lingual frenectomy, in addition to improved sleep. A retrospective cohort concluded that lingual frenuloplasty combined with myofunctional therapy is effective in the treatment of snoring and mouth breathing. Conclusion: The studies included in this review contribute to corroborate the association between ankyloglossia and obstructive sleep apnea.
Keywords: Ankyloglossia; Myofunctional therapy; Obstructive sleep apnea